Social networks peacebuilding event mining: a systematic literature review - Shaikh, Muniba; Salleh, Norsaremah; Abdulllah, Lili Marziana (2014)
Social Networks (SNs) becomes a major source of reporting new events happens in real life even before the news channels and other media sources nowadays. The objective of this paper is to get insight of peacebuilding (Pb) event mining (EM) from SNs (e.g., tweets, Fb posts, etc) by conducting the systematic Literature (SLR) process. The paper aims to answer some research questions (RQs) that includes: 1) Which SN's has been widely used for Textual PbEM?; 2)What Context or setting has been focussed of PbEM studies and how to catagorize Pb events?, and 3) What other types of events are reported? The SLR process has been used to identify the related literature and for analysis of evidences in order to answer the RQs. This paper concluded on the basis of SLR studies that the "twitter" is the most frequently used SN for Textual Peacebuilding Event Mining (PbEM) because 54 out of 64 studies on PbEM uses Twitter. SLR resulted that earth quake (EQ) events are the major concerned events that eect country's economy and peace as compare therefore most of studies uses the EQ as context/setting. The paper presents the details on categories of Pb events, contexts/settings and the list of other types of events or topics that are the center of the research nowadays based on synthesis of evidences.